A comparison of the financial performance of the islamic and conventional bank in Malaysia / Nur Fatihah Abdul Latif - Abdul Latif, Nur Fatihah (2018)
This paper is to study a compares their respective profitability in terms of volume and volatility of their deposits and loans in Malaysia in a five year period from 2012 to 2016 and analyze the with panel data regression analysis. This study focused on six local Islamic and conventional banks in Malaysia. The internal factors (bank specific) that effect towards profitability are including volatility of bank deposits, volume of deposits, volatility of bank loans, and volume of loans. Hence, volume of deposit, volatility of deposit, volume of loans, and volatility of loans does not have a significant impact on banks profitability in Malaysia.